2021
DOI: 10.3389/fonc.2020.615203
|View full text |Cite
|
Sign up to set email alerts
|

ALT Flare Predicts Hepatocellular Carcinoma Among Antiviral Treated Patients With Chronic Hepatitis B: A Cross-Country Cohort Study

Abstract: ObjectivesAlanine aminotransferase (ALT) level is one of the crucial indexes to evaluate disease status for chronic hepatitis B (CHB) patients. However, whether the ALT level after nucleos(t)ide analog (NA) treatment is associated with hepatocellular carcinoma (HCC) development remains unclear.Materials and MethodsWe evaluated the association between ALT level and HCC occurrence in NA-treated patients and investigated the predictive value of ALT flare for HCC. The associations between ALT level and HCC were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…32 It also has important clinical significance in the prognosis of cancer. 33 An increase in the ALT is a predictor of HCC development; 34 previous researches demonstrated that patients with HCVassociated cirrhosis with a sustained high serum ALT level were at high risk for HCC development and those with a low ALT level were at low rate of development of HCC. [35][36] Induction of membrane lipid peroxidation by the released free radicals and stimulation of inflammation is followed by hepatic cell damage and excessive release of ALT.…”
Section: Discussionmentioning
confidence: 99%
“…32 It also has important clinical significance in the prognosis of cancer. 33 An increase in the ALT is a predictor of HCC development; 34 previous researches demonstrated that patients with HCVassociated cirrhosis with a sustained high serum ALT level were at high risk for HCC development and those with a low ALT level were at low rate of development of HCC. [35][36] Induction of membrane lipid peroxidation by the released free radicals and stimulation of inflammation is followed by hepatic cell damage and excessive release of ALT.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Du al. [32] observed the risk of HCC in patients with ALT elevation (1.82-2.75-fold). Individuals with chronic HBV who had chronically abnormal ALT may have been included in or referred to by the population that had high ALT.…”
Section: Discussionmentioning
confidence: 93%
“…It has been showed in previous studies that ALT, Age, PLT and LS were independent variables for severity of liver injury [ 25 27 ]. In the study, we also found that there are positive correlations between these indexes and liver injury, in agreement with the previous reports.…”
Section: Discussionmentioning
confidence: 99%